A systematic review on the comparison of the safety and efficacy of temozolomide and radiotherapy along with another drug combination in the treatment of glioblastoma multiforme - Chowdhury, Shamima Zerin (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.